Implementación de un Sensor de Nivel en el Tanque Industrial 334HP9004 en Minera Panamá Área de Flotación Columnas (2023)
In the execution of this project, it is sought to provide a solution to conditions that are fundamental in Instrumentation and Control, such as the reliability of the operation of the instrument due to its different conditions in which it is exposed and also that it provides a correct response to what an organization looks at its cost/benefit processes given the universe of brands and technologies that may be unsustainable for many industries. Finally, and no less important, is the ability to select the sensor that, within the control options, provides us with a transparent and noise-free measurement that allows the control to be executed towards the pumps in real time to maintain the level of the tank automatically and stable.